BIO MANAGEMENT OF FALL ARMYWORM USING METARHIZIUM ANISOPLIAE - REHMAN, HU; SAHI, GM; ALI, Q; SAGHEER, M (Biological and Clinical Sciences Research Journal, 2024)
Agriculture is the backbone of Pakistan. However, the recent threat to cash crops of Pakistan is fall armyworm (Spodoptera frugiperda). The farmers used various types of insecticides for the effective management of fall armyworm. Due to the environmental hazards associated with the pesticides, it is necessary to reduce the use of synthetic pesticides and develop novel strategies for the management of insect pests especially fall armyworm. The diseases caused by fungi in insects commonly; reduce populations significantly, demonstrating that bio-insecticides may be a viable option for solving the problems of insect pests in agriculture. Among the fungi used as biological insecticides Metarhizium anisopliae has been widely used. Therefore, the current research study was conducted to manage the fall armyworm using Metarhizium anisopliae. The fungus was cultured under lab conditions and various concentrations were prepared. The four concentrations with three replications were applied on the larval or pupal stages of fall armyworm by using dip and foliar application methods. The mortality was recorded after 24, 48, 72 and 96 hours of application. The data were arranged and analyzed using suitable statistical software. The homogenous mean was analysed using Tuckey HSD (p<0.05). The results showed that the higher concentration of M. anisopliae was more effective as compared to lower concentrations both in lab and field conditions. The highest percentage mortality of 3rd, 4th, 5th and late instar larvae of fall armyworm was recorded as 98.663±0.66, 93.550±0.22, 87.333±0.14 and 84.440±0.11 %, respectively, after the treatment of 1×108 conidia/ml and 12 days of exposure period. After 12 days the maximum reduction in FAW population was recorded (0.500±0.28 larvae/five plants) by the treatment of EPF (1×108 conidia/ml) after 12 days of exposure, which was significantly different form other treatments. The minimum reduction of fall armyworm larvae was recorded (3.00±1.22 larvae/ five plants) after the treatment of EPF at 1×106 conidia/ml. In conclusion, the Metarhizium anisopliae considered as ecofriendly approach to manage the fall armyworm in maize crop and can be used in integrated pest management programs.